Anal fissure treated ambulatorily by means of partial lateral internal sphincterectomy.: A propósito de 43 casos. - Estefan, Alberto; Carriquiry, Guillermo; Lago, Fernando; Falchetti, Juan C; Grezzi, Roberto (Cirugía del Uruguay, 1985)
Analysis of a series of 43 patients with anal fissure treated ambulatorlly by means of partial lateral interna! sphyncteroctomy. Rational and selectiva use of this therapeutic option results in quick and simple alleviation of symptoms, as well as definitive cure of the disease.